Studi Komparasi Bauran Pemasaran Pasar Tradisional dan Pasar Modern di Kecamatan Ambulu - Alawiyah, Tsamrotul; Pudjiastutik, Endang Wahyu (Program Studi Agribisnis, 2023)
The ever-increasing developments in both the economic and technological sectors, require business people to continue to innovate in order to maintain their position, including business players in traditional markets. The purpose of this study is to find out how the traditional market marketing strategy and also to compare the marketing mix strategy between traditional markets and modern markets. In this study using a qualitative method with purposive sampling. Research results: 1) Traditional market marketing strategies for products sold are still partially sold with the latest models. Prices are determined based on a bargaining process. The location is easily accessible by consumers and close to the center of the crowd and is strategic. The promotions carried out are still not effective and not maximized because they are still using word of mouth promotion. 2) comparison of marketing strategies, traditional markets sell low quality and standard goods, goods sold are less varied and incomplete and goods that have been purchased may be exchanged, prices are not listed on the product, prices are negotiable, prices offered are inconsistent, prices are relatively cheap and direct payments to traders, the product location is not neat, it is located in the middle of a residential area, the place is narrow, cleanliness is not maintained and many public transportation passes, services are assisted by traders, promotions are carried out by word of mouth and rarely use social media. In the modern market, the goods sold are of standard and high quality, the goods sold are varied and in large quantities and the goods that have been purchased cannot be exchanged, the prices are listed on the products so that they are non-negotiable, the prices offered are consistent, the prices are relatively higher and the payment is made at the cashier. product location is neatly arranged, located in strategic locations tend to be crowded, the place is spacious, cleanliness is more maintained and many public transportation passes, services are carried out independently, promotions carried out include: discounts, buy 1 get 1 free, gift vouchers, raffle coupons and promotions done online using social media.